Beschreibung neuer Arten aus der Gattung Caulotrupis Wollaston, 1854 (Coleoptera: Curculionidae: Cossoninae) von den Makaronesischen Inseln - Stüben, Peter E. (Contributions to Entomology = Beiträge zur Entomologie, 2018)
Eight new species of the Macaronesian genus Caulotrupis Wollaston, 1854 are described and distinguished from the related species: C. ficvorator spec. nov. (Madeira), C. ficvorator isambertoi ssp. nov. (Deserta Grande), C. portosantoensis spec. nov. (Porto Santo), C. lucifugus faialensis ssp. nov. (north of Madeira), C. xerophilus spec. nov. (Porto Santo, Ilheu Chao), C. xerophilus desertagrandensis ssp. nov. (Deserta Grande), C. lourencoensis spec. nov. (Ponta de Sao Lourenco) and C. wollastoni spec. nov. (Deserta Grande). A distribution map with entries and photos (focus stacking) of the habitus, aedeagus and female genitalia of all new taxa are presented. Molecular data on the p-distances of the mitochondrial COI gene support the morphological analyses. It is a preparatory study into a major revision of the genus Caulotrupis in the Snudebiller Journal. Nomenclatural Acts Caulotrupis ficvorator spec. nov. – urn:lsid:zoobank.org:act: B9CE3583-6370-45C8-B128-638511C94260 Caulotrupis ficvorator isambertoi ssp. nov. – urn:lsid:zoobank.org:act: B79B3F8C-E522-427C-9500-1B3DD49E8A17 Caulotrupis portosantoensis spec. nov. – urn:lsid:zoobank.org:act: 5E10063F-08A9-4853-9DEE-1FBB327E97EC Caulotrupis lucifugus faialensis ssp. nov. – urn:lsid:zoobank.org:act: 66433AA4-BFFC-46F5-82E0-304EC11DAE64 Caulotrupis xerophilus spec. nov. – urn:lsid:zoobank.org:act: 8EF361E2-8F59-4BE3-B426-B2608993AC7A Caulotrupis xerophilus desertagrandensis ssp. nov. – urn:lsid:zoobank.org:act: 86BB811D-B03A-4980-97BF-22B02E5DF0BB Caulotrupis lourencoensis spec. nov. – urn:lsid:zoobank.org:act: BAFCE97F-5B0F-4109-A71D-D6A8FEA01391 Caulotrupis wollastoni spec. nov. – urn:lsid:zoobank.org:act: A093E31C-FD95-46B2-9807-7540212DF15A